Effects of Electronic Procurement on Service Quality in Kisumu County Government, Kenya - Teresa Achieng Akuno, Passy (Jooust, 2023)
Organizations invest huge sums of money on technological applications with the aim of gaining competitive advantage, both at manufacturing and service delivery phases. Thus, technology has changed the landscape of operations in organizations and governments. In supply chain r e l a t e d se r vi c e s , e-procurement is adopted for acquisition of goods and services in order to facilitate objectivity in identification, product selection and payment inclusive of post-contract payment activities like contract administration and supplier relationships. The national government introduced e-procurement module in the County governments to decrease inefficiencies in public procurement. However, limited research has addressed the effect of electronic procurement on service quality in Kisumu County. To close this gap, this study set out to evaluate the effect of e-procurement on service quality. Objectives of the study included: to determine the effect of e-sourcing- tendering and e-reverse auctioning on service quality, in Kisumu County government Kenya. The target population was 97 suppliers and clients of Kisumu County government. Seventy-eight suppliers and customers were chosen at random to form the sample size, and they each received a standardized questionnaire. The Technology Acceptance Model, SERVQUAL Model and Dynamic Capability theory was used to guide the study. An explanatory research design was selected for the study. When assessing the instrument's internal dependability, a Cronbach's Alpha coefficient of 0.81 was discovered. Quantitative data were analyzed using descriptive and infere ntial methods. Quantitative data were analyzed using descriptive and inferential methods. The level of significance between e-procurement and service quality was tested using linear regression. The research found that e-procurement improved service quality (R=0.534). The research's findings showed that e-procurement significantly affected service quality (p=0.001; sig. value=0.05). E-tendering was ranked first in affecting service quality (β=0.94) and had a significant effect on service quality (p=0.000). E-sourcing rated second in affecting service quality (p=0.001) and had a significant effect on the provision of quality services (p=0.001). E-reverse auctioning rated third in affecting service quality (β=0.324) and had a substantial effect on service quality as well (p=0.000). The county government and competent authorities will utilize the study's findings to help them decide what steps to take to enhance quality of service delivery through e-procurement. In addition, it is very important for the e-procurement consumers, practitioners, and institutions to evaluate the various e-procurement components employed with the goal of optimizing their procurement systems. In this study, the primary e-procurement elements in the Kisumu County government were examined: e-sourcing, e-tendering, and e-reverse auctioning. To attain the total service quality, the researcher advises that a similar study be conducted in sectors other than county governments utilizing additional e-procurement components, and that the county governments strengthen their use of e-procurement.
Keywords: Effect of e-procurement on service quality.; Effects of Electronic Procurement on Service Quality